1998
DOI: 10.1037/0735-7028.29.2.130
|View full text |Cite
|
Sign up to set email alerts
|

Rafting the rapids: Occupational hazards, rewards, and coping strategies of psychotherapists.

Abstract: In today's market, clinical practitioners have complex and demanding jobs. This survey study identified contemporary occupational hazards, rewards, and coping strategies of 208 psychotherapists and the interrelationships among these variables. Unexpected post hoc gender differences revealed that female therapists reported significantly more rewards and coping strategies than men. Suggestions are offered for how practitioners can promote their own job satisfaction. Implications for supervisors and trainers of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
76
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(97 citation statements)
references
References 18 publications
20
76
1
Order By: Relevance
“…Self-care behaviours can take various forms such as self-awareness: Acknowledging potential blind-spots and weaknesses (Barnett, Baker, Elman, & Schoener, 2007); self-acceptance or selfcompassion: The ability to be caring and understanding towards oneself (Neff, 2009); and supervision from peers or a superior (Coster & Schwebel, 1997). Less formal activities are also considered self-care behaviours, such as engaging in physical activities, spending time with friends and family, and taking breaks between sessions (Kramen-Kahn & Hansen, 1998;Stevanovic & Rupert, 2004). Collectively, these activities have been labelled career-sustaining behaviours (CSBs; Stevanovic & Rupert, 2004).…”
mentioning
confidence: 99%
“…Self-care behaviours can take various forms such as self-awareness: Acknowledging potential blind-spots and weaknesses (Barnett, Baker, Elman, & Schoener, 2007); self-acceptance or selfcompassion: The ability to be caring and understanding towards oneself (Neff, 2009); and supervision from peers or a superior (Coster & Schwebel, 1997). Less formal activities are also considered self-care behaviours, such as engaging in physical activities, spending time with friends and family, and taking breaks between sessions (Kramen-Kahn & Hansen, 1998;Stevanovic & Rupert, 2004). Collectively, these activities have been labelled career-sustaining behaviours (CSBs; Stevanovic & Rupert, 2004).…”
mentioning
confidence: 99%
“…Unlike many other studies that have made brief comparisons of humor to job burnout among mental health therapists (Kramen-Kahn and Hansen 1998;Rupert and Kent 2007;Stevanovic and Rupert 2004), this study provided an opportunity to study the specific characteristics of both variables, and how characteristics correlated with each other.…”
Section: Discussionmentioning
confidence: 96%
“…From a survey group of 595 psychologists, Rupert and Kent (2007) found that maintaining a sense of humor was rated the most important career-sustaining behavior out of 25 behaviors. In a similar study, Kramen-Kahn and Hansen (1998) noted that out of 208 psychotherapists, eighty-two percent (n = 171) rated maintaining a sense of humor to be most important in sustaining a successful career. In another study, two hundred and eightysix licensed psychologists rated a sense of humor among the four top strategies to use in combating career stressors (Stevanovic and Rupert 2004).…”
Section: Introductionmentioning
confidence: 93%
“…Numerous studies have found an inverse correlation between social support in an organization and the development of burnout (Cherniss, 1980;Dietzel & Coursey, 1998;Etzion, 1984;Himle, Jayaratne, & Chess, 1987;Himle, Jayaratne, & Thyness, 1989;Jackson & Schuler, 1983;Jayaratne, Tripodi, & Chess, 1983;Kramen-Kahn & Hansen, 1998;Maslach & Jackson, 1981;Maslach & Pines, 1977;Pines & Maslach, 1978;Russell, Altmaier, & Van Velzen, 1987;Shinn, Rosario, Morch, & Chestnut, 1984;Wade, Cooley, & Savicki, 1986;Winnibust, 1993). Many have found this effect to be related to both supervisor support and co-worker support, noting that "decreased emotional support from supervisors and co-workers was predictive of irritation, emotional exhaustion, and depersonalization .…”
Section: Organizational Characteristicsmentioning
confidence: 91%